Meniscus Regeneration With Multipotent Stromal Cell Therapies - Zhou, Yun-Feng; Zhang, Di; Yan, Wan-Ting; Lian, Kai; Zhang, Zheng-Zheng (Frontiers in Bioengineering and Biotechnology, 2022)
Meniscus is a semilunar wedge-shaped structure with fibrocartilaginous tissue, which plays an essential role in preventing the deterioration and degeneration of articular cartilage. Lesions or degenerations of it can lead to the change of biomechanical properties in the joints, which ultimately accelerate the degeneration of articular cartilage. Even with the manual intervention, lesions in the avascular region are difficult to heal. Recent development in regenerative medicine of multipotent stromal cells (MSCs) has been investigated for the significant therapeutic potential in the repair of meniscal injuries. In this review, we provide a summary of the sources of MSCs involved in repairing and regenerative techniques, as well as the discussion of the avenues to utilizing these cells in MSCs therapies. Finally, current progress on biomaterial implants was reviewed.